Nothing stopped Sophie the story of unshakable mathematician Sophie Germain - Bardoe, Cheryl 1971- (Little, Brown and Company, 2018)
A biography of Sophie Germain, who grew up during the French Revolution and followed her dream of studying mathematics, becoming the first woman to win a grand prize from the Royal Academy of Sciences and changing the world with her discoveries....
Keywords: Germain, Sophie -- 1776-1831; Women mathematicians -- France -- Biography -- Juvenile literature; Mathematicians -- France -- Biography -- Juvenile literature; Mathematics -- France -- History -- 19th century -- Juvenile literature; Bildband